Osteoma of the Pharynx That Developed from the Hyoid Bone - Akira Hagiwara; Noriko Nagai; Yasuo Ogawa; Mamoru Suzuki (Case Reports in Otolaryngology)
This paper reports on apparently the first case of a pharyngeal osteoma that developed from the hyoid bone. An 84-year-old man’s, presenting symptom was a slight throat pain. Endoscopic examination revealed a huge mass occluding the pharyngeal space. CT scan of the neck showed a large osseous mass adjacent to the hyoid bone. Transoral resection with tracheostomy was performed. Histopathologically, the tumor consisted of mature lamellar bone without a fibrous component. For two years postoperatively, the patient has been free from throat symptoms and signs of recurrence. Osteomas are benign, slow-growing tumors. They rarely develop symptoms or cause functional disturbance. We performed total resection to avoid further functional disturbance as the osteoma was huge. To the best of our knowledge, this is the first report on an osteoma that occupied the pharyngeal space and developed from the hyoid bone.